Wai Selabung geothermal reservoir analysis based on gravity method - Sarkowi, Muh; Wibowo, Rahmat Catur; Sawitri, Regina Febryzha; Mulyanto, Bagus Sapto (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
Research has been conducted using the gravity method in the Wai Selabung area, South Ogan Kemiring Ulu Regency, South Sumatra Province, correlated with geological data, magnetotellurics, and geochemical data. This research aims to get structural patterns, subsurface models and identify the heat source and reservoir areas of the Wai Selabung geothermal system. This study uses the gravity method to model the subsurface, which is correlated with magnetotelluric and geochemical data to identify reservoir prospect areas. The results obtained from this research include residual anomalies in the research area showing the presence of a northwest-southeast trending fault structure by the main fault structure of this area trending northwest-southeast and slightly southwest-northeast. Analysis of the Second Vertical Derivative value of zero indicates the boundaries of the geothermal reservoir in the middle of the research area.  The results of the 3D inversion modeling of the research area show that low density (2 to 2.15 g/cm3) indicates the location of the reservoir, medium-density values (2.2 to 2.4 g/cm3) are tertiary sandstone sedimentary. The high-density distribution value (2.5 to 2.9 g/cm3) indicates a potential heat source. And based on the analysis of the gravity method correlated with geological data, magnetotelluric, and geochemical data, the prospect area for the Wai Selabung geothermal reservoir, is around Teluk Agung, Perekan, and Talang Tebat.